Administration guidelines for quality public and community radio broadcasting in Thailand - Rawd-ard, Pansa (Siam Communication Review, 2025)
The purpose of this study was to study the appropriate approaches for the operation of public and community broadcasting in Thailand. Through the analysis of concepts related to the administration of broadcasting both in Thailand and abroad from collecting data in the form of public hearings from relevant stakeholders and a population survey of 1,010 sets in 4 regions: central, Bangkok and its vicinity, northeastern, southern and northern regions. The results of the study from the public hearing under 8 issues that will make public and community service broadcasting stations have quality are: 1. Policies/Guidelines 2. Supervision 3. administration of radio stations 4. Contents 5. Program format 6. Finance and source of funds/income generating 7. Principles of a quality radio station and 8. Other related issues. The study results from the survey found a suitable guideline for the operation of radio broadcasting stations that is good and should be suitable for Thailand, different from the public hearing, consisting of 5 elements: 1. Organizational management 2. Program content 3. Program format 4. Programming 5. The principle of a safe and creative radio station. along with providing policy recommendations, namely No one size fits all, Force/Drive, Upskill & Reskill, Partnership, Great Value, Excellent Relationships, Mentors and Guide.